Fostering Inclusive Growth in Turkey by Promoting Structural Change in the Business Sector - Gönenç, Rauf (OECD Economics Department Working Papers, 2014)
Turkey's business sector dynamism has underpinned broad-based and inclusive growth in the 2000s. However, the business sector is highly segmented, with a relatively small core of modern high-productivity corporations, and myriad small, less formal and low-productivity entities. This hampers efficient resource allocation and tends to entrench social inequalities. It also makes it difficult to build on-the-job human capital for the large number of low-skilled. This segmentation needs to be overcome to raise productivity in the informal, low-skill and low-productivity sector, and to facilitate resource transfers from low to higher productivity businesses. This ought to be achieved by aligning Turkey's formal regulatory and tax framework with OECD best practice, rather than through "second-best" arrangements where noncompliance with rules co-exists with selective subsidies to parts of the formal sector. Labour market and business taxation reforms are particularly important to enable all categories of enterprises to operate flexibly on a rule-based, level playing field and to achieve productivity enhancing and socially inclusive restructuring